Smart complaints for android - Nursaifullah, Mat Nor @ Abd Rahim (2014)
This project is to design an Android application that will act as a medium for the students to lodge reports related to any dissatisfaction on the services in the campus and so forth. For example, a student found that the meal he bought from the cafeteria is molded or one of the equipment in the gym has broken, so he can simply just take a photo of it and upload it into the system. This project will be developed using Eclipse. This project is chosen because I find it as a very interesting project. Furthermore, it is also very practically feasible to construct, practically applicable and useful and has the potential to be marketed. In addition, it is different from other existing similar systems in the market. Java programming is the language used in developing Smart Complains. It was chosen because it gives more structured approach rather than the conventional way. The reports which have been uploaded will be managed in a web application designed for the administrators. The final product of this project is a fully functional application that achieves the initial objectives of this project and at the same time illustrates the practical feasibility of our idea. However, since the main objective is only to illustrate the feasibility of our idea, therefore the specification and quality of certain components have been compromised to reduce the project cost. But, in the real life situation, the specifications of certain components have to be changed for optimum and satisfactory performance.